2018
DOI: 10.7567/apex.11.063101
|View full text |Cite
|
Sign up to set email alerts
|

Promising critical current density characteristics of Ag-sheathed (Sr,Na)Fe2As2 tape

Abstract: We report the fabrication of (Sr,Na)Fe 2 As 2 superconducting tapes by the powder-in-tube technique and their characteristics, including the transport critical current density J c at 4.2 K up to 140 kOe, the magnetic J c estimated from magnetic hysteresis curves, magneto-optical (MO) images, and scanning electron microscopy images. In a tape sintered at 875 °C for 1 h, the transport J c reaches 26 kA/cm 2 at 4.2 K and 100 kOe for a field perpendicular to the tape surface. When the field is parallel to the tape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Iyo et al reported that the transport J c for (Sr,Na)Fe 2 As 2 tapes at 20 K under a magnetic field of 25 kOe was superior to that for (AE',K)Fe 2 As 2 tapes [41]. The transport J c for (Sr,Na)Fe 2 As 2 tapes of 26 kA cm −2 at 4.2 K under 100 kOe, and that for (Ba,Na)Fe 2 As 2 tapes of 40 kA cm −2 at 4.2 K under 40 kOe, were also reported [42,45]. Very recently, J c in (Ba,Na)Fe 2 As 2 HIP round wire reached 150 and 20 kA cm −2 at self-field and 100 kOe, respectively [46][47][48].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Iyo et al reported that the transport J c for (Sr,Na)Fe 2 As 2 tapes at 20 K under a magnetic field of 25 kOe was superior to that for (AE',K)Fe 2 As 2 tapes [41]. The transport J c for (Sr,Na)Fe 2 As 2 tapes of 26 kA cm −2 at 4.2 K under 100 kOe, and that for (Ba,Na)Fe 2 As 2 tapes of 40 kA cm −2 at 4.2 K under 40 kOe, were also reported [42,45]. Very recently, J c in (Ba,Na)Fe 2 As 2 HIP round wire reached 150 and 20 kA cm −2 at self-field and 100 kOe, respectively [46][47][48].…”
Section: Introductionmentioning
confidence: 75%
“…In contrast to K-doped 122-type materials, the investigation of J c of single crystals and the fabrication of wires or tapes of Na-doped 122-type material, (AE,Na)Fe 2 As 2 (AE = Ba, Sr, or Ca) [37][38][39][40], have not been performed extensively, in spite of their comparable T c (∼34 K) to K-doped ones. Only recently, some studies of tapes and wires of (AE,Na)Fe 2 As 2 have been reported [41][42][43][44][45][46][47]. Iyo et al reported that the transport J c for (Sr,Na)Fe 2 As 2 tapes at 20 K under a magnetic field of 25 kOe was superior to that for (AE',K)Fe 2 As 2 tapes [41].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the fabrication of Na-doped SrFe 2 As 2 tapes and their promising J c characteristics have been reported recently. [35][36][37][38] Iyo et al reported that the transport J c for Na-doped SrFe 2 As 2 tapes at 20 K under a magnetic field of 25 kOe is superior to that for K-doped AEFe 2 As 2 tapes. 35) Suwa et al reported that the transport J c for Na-doped SrFe 2 As 2 tapes reaches 26 kA cm −2 under 100 kOe at 4.2 K. 36) Recently, new types of IBSs, e.g., the 1144 type with CaKFe 4 As 4 , have been developed.…”
mentioning
confidence: 99%
“…[35][36][37][38] Iyo et al reported that the transport J c for Na-doped SrFe 2 As 2 tapes at 20 K under a magnetic field of 25 kOe is superior to that for K-doped AEFe 2 As 2 tapes. 35) Suwa et al reported that the transport J c for Na-doped SrFe 2 As 2 tapes reaches 26 kA cm −2 under 100 kOe at 4.2 K. 36) Recently, new types of IBSs, e.g., the 1144 type with CaKFe 4 As 4 , have been developed. 39) The structure of CaKFe 4 As 4 is similar to that of 122-type IBSs, and the Ca and K layers stack alternately along the c-axis.…”
mentioning
confidence: 99%
“…ron−based superconducting wires/tapes with superconducting critical temperature (T c ) > 20 K fabricated via the powder−in−tube (PIT) process, 1) were reported for ReFeAsO 1−x F x 2-4) (Re: Rare earth elements), Ae 1−x A x Fe 2 As 2 [5][6][7][8] (Ae: Alkali earth elements, A: Alkali elements), AeAFe 4 As 4 [9][10][11] and Sr 2 VFeAsO 3−δ . 12) In addition, superconducting tapes using FeSe 1−x Te x were reported 13,14) as well, though their T c s were lower than 20 K. Although the T c s of these iron−based superconductors are lower than those of cuprate superconductors, their upper critical magnetic fields (μ 0 H c2 ) are comparable.…”
mentioning
confidence: 99%